Analisis Kesalahan Siswa dalam menyelesaikan Soal model PISA - hartatiana hartatiana; Tri Artati; Ambarsari Kusuma Wardani (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to find out the mistakes made by students in solving the PISA model questions based on the Newman procedure. This research is a qualitative research. The research subjects consisted of 15 of ninth grade students SMP Karya Ibu Palembang. Data was collected by tests and interviews. The validity of the data was tested by using triangulation technique. The data were analyzed with data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are errors made by ninth grade students in solving the PISA model questions. These errors include misunderstanding the problem, problem transformation error, process skill error and writing answer error. Therefore, to minimize the occurrence of errors, it is recommended that students understand the formula by being understood not memorized, learning is more related to everyday life to make it easier to understand and remember, and increase practice questions.